2016
DOI: 10.1002/ppul.23570
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory syncytial virus hospitalization and mortality: Systematic review and meta‐analysis

Abstract: SummaryBackground: Respiratory syncytial virus (RSV) is a major public health burden worldwide. We aimed to review the current literature on the incidence and mortality of severe RSV in children globally. Methods: Systematic literature review and meta‐analysis of published data from 2000 onwards, reporting on burden of acute respiratory infection (ARI) due to RSV in children. Main outcomes were hospitalization for severe RSV‐ARI and death. Results: Five thousand two hundred and seventy‐four references were ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
219
2
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(248 citation statements)
references
References 61 publications
15
219
2
12
Order By: Relevance
“…As a result, we cannot determine if the incidence rates in preterm infants are higher than those of term infants. However, the incidence or RSV‐confirmed (62.6 per 1000 child‐years) and RSV‐attributable admissions (94.1 per 1000 child‐years) in our study are similar to those reported worldwide during the first year of life in preterm infants (63.85, 95% CI 37.52‐109.7, hospitalizations per 1000 children per year) . In contrast, the global incidence of RSV hospitalizations in all children <1 year of age was estimated at 19.19 (95% CI 15.05‐24.48) per 1000 children per year.…”
Section: Discussionsupporting
confidence: 84%
“…As a result, we cannot determine if the incidence rates in preterm infants are higher than those of term infants. However, the incidence or RSV‐confirmed (62.6 per 1000 child‐years) and RSV‐attributable admissions (94.1 per 1000 child‐years) in our study are similar to those reported worldwide during the first year of life in preterm infants (63.85, 95% CI 37.52‐109.7, hospitalizations per 1000 children per year) . In contrast, the global incidence of RSV hospitalizations in all children <1 year of age was estimated at 19.19 (95% CI 15.05‐24.48) per 1000 children per year.…”
Section: Discussionsupporting
confidence: 84%
“…CFR meta‐estimates for 2015 in infants 0‐5 and 6‐11 months of age in developing countries were 2.2 (1.8‐2.7) and 2.4 (1.9‐3.2), respectively . A second meta‐analysis identified the highest case fatality rates in Kenya, Morocco, South Africa, and Mozambique …”
Section: In‐hospital Mortality Due To Rsv In Developing Countriesmentioning
confidence: 97%
“…RSV disease manifestations can vary from mild URTI to severe pneumonia or bronchiolitis, which can lead to hospitalization and serious complications like respiratory failure [86]. Despite the high incidence of bacterial and RSV co-infection in both children and adults, only few studies aimed to investigate the possible interactions between S. aureus and this virus [8790].…”
Section: Mechanisms Involved In Interactions Between Staphylococcus Amentioning
confidence: 99%